Two state-of-the-arts current-mode ternary full adders based on CNTFET Technology - Mona Moradi (Institute of Advanced Engineering and Science, 2020)
Adder core respecting to its various applications in VLSI circuits and systems is considered as the most critical building block in microprocessors, digital signal processors and arithmetic operations. Novel designs of a low power and complexity Current Mode 1-bit Full Adder cell based on CNTFET technology has been presented in this paper. Three major parts construct their structures; 1) the first part that converts current to voltage; 2) threshold detectors (TD); and 3) parallel paths to convey the output currents flow. Adjusting threshold voltages which are significant factor for setting threshold detectors switching point has been achieved by means of CNTFET technology. It would bring significant improvements in adjusting threshold voltages, regarding to its unique characterizations. Simple design, less transistor counts and static power dissipation and better performance comparing previous designs could be considered as some advantages of the novel designs.